Pengaruh Aplikasi Android Aneminfo terhadap Pengetahuan dan Sikap Remaja Putri terkait Anemia Defisiensi Besi - Rizki Septia Saraswati; Apoina Kartini; Farid Agushybana (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Iron deficiency anemia is one of the nutritional problems that still occur in Indonesia which is common in young women. Early nutrition education is needed to prevent these problems. The purpose of this study was to analyze the effect of the android-based educational media